2018
DOI: 10.1089/brain.2018.0633
|View full text |Cite
|
Sign up to set email alerts
|

Problem Drinking, Alcohol Expectancy, and Thalamic Resting-State Functional Connectivity in Nondependent Adult Drinkers

Abstract: Alcohol misuse is associated with thalamic dysfunction. The thalamus comprises subnuclei that relay and integrate information between cortical and subcortical structures. However, it is unclear how the subnuclei contribute to thalamic dysfunctions in problem drinking. We investigated resting-state functional connectivity (rsFC) of thalamic subregions in 107 nondependent drinkers (57 women), using masks delineated by white matter tractography. Thalamus was parceled into motor, somatosensory, visual, premotor, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 118 publications
2
18
1
Order By: Relevance
“…The important roles of the thalamus in alcohol dependence have been revealed by previous studies (Gilman, Smith, Ramchandani, Momenan, & Hommer, 2012;Hu, Ide, Zhang, Sinha, & Chiang-shan, 2015;Schmaal et al, 2013;Zhornitsky et al, 2018), such as the implications of the modular dysfunction and structural deficits of thalamus in reward processing and cognitive control (Chanraud et al, 2007;Grodin & Momenan, 2017;Pitel, Segobin, Ritz, Eustache, & Beaunieux, 2015). Disruptions to these psychological processes are critical features of alcohol dependence, and the thalamus appears to be particularly vulnerable to the influence of alcohol (Pitel et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…The important roles of the thalamus in alcohol dependence have been revealed by previous studies (Gilman, Smith, Ramchandani, Momenan, & Hommer, 2012;Hu, Ide, Zhang, Sinha, & Chiang-shan, 2015;Schmaal et al, 2013;Zhornitsky et al, 2018), such as the implications of the modular dysfunction and structural deficits of thalamus in reward processing and cognitive control (Chanraud et al, 2007;Grodin & Momenan, 2017;Pitel, Segobin, Ritz, Eustache, & Beaunieux, 2015). Disruptions to these psychological processes are critical features of alcohol dependence, and the thalamus appears to be particularly vulnerable to the influence of alcohol (Pitel et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…In men, connectivity between thalamus and salience and executive control regions correlated with AUDIT scores (Zhornitsky et al, 2018). In women, thalamic connectivity to posterior cingulate cortex correlated with AUDIT scores (Zhornitsky et al, 2018).…”
Section: Adulthoodmentioning
confidence: 98%
“…Neuroadaptations related to AUD in these regions may be related to maladaptive regulation of neural circuits related to reward and cognition and may have implications for the likelihood of high-risk drinking in response to alcohol cues. For example, a recent resting state fMRI study found that drinking was associated with SG differences in thalamic connectivity in relation to AUDIT scores (Zhornitsky et al, 2018). In men, connectivity between thalamus and salience and executive control regions correlated with AUDIT scores (Zhornitsky et al, 2018).…”
Section: Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…As with previous work with similar task designs, 25,26 we distinguished food and nonfood image blocks for each subject using a general linear model (GLM) which included the realignment parameters in all six dimensions. We corrected for serial autocorrelation caused by aliased cardiovascular and respiratory effects by the FAST model.…”
Section: Imaging Data Modelingmentioning
confidence: 99%